مدى فعالية الحكم الراشد و الجوانب الدولية والإجتماعية في إطار الإصلاحات الإقتصادية للجيل الثاني في الجزائر - nasir, ahmed; Serdouk, fateh (Finance and Business Economies Review, 2018)
This study aims to highlighting the experience of good governance in the Maghreb countries (Algeria, Tunisia), through the knowledge of the reality of good governance as well as the mechanisms of good governance .All these measures came in parallel with the governance system, fighting corruption and exercising authority and responsibility within the institutional framework, of its mechanisms and its assessment through Kaufman's indicators, in light of the second generation of economic reforms by dropping the items of Washington's broad consensus and the extent to which the international and social aspects of these countries succeed